PSYCHOLOGICAL ASPECTS OF REMOTE TEAM MANAGEMENT - Обозна, А.О.; Яковуник, О.В.; Яковуник, Д.І. (SWorldJournal, 2026)
The article examines the psychological aspects of managing remote teams in the context of digital transformation and hostilities in Ukraine. Key problems arising in the process of remote work are identified, including a decrease in the level of social int